2017
DOI: 10.1039/c7cp02762a
|View full text |Cite
|
Sign up to set email alerts
|

B–H⋯π: a nonclassical hydrogen bond or dispersion contact?

Abstract: Highlighting research from the Computational Chemistry group of Prof. Pavel Hobza, IOCB Prague, Czech Republic B-H … π: a nonclassical hydrogen bond or dispersion contact?Herein, we re-interpret the nature of B−H … π contacts between closo-C 2 B 10 H 12 carborane and phenyl in Ir-dithiolene-phosphine complexes. These interaction motifs have recently been crystallographically observed and proposed as a new type of electrostatically driven nonclassical hydrogen bonding. By means of advanced quantum chemistry on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 47 publications
3
34
0
Order By: Relevance
“…For example, in case of F‐substituted DB, favorable interaction (positive ΔE values) is predicted from B3LYP functional which encounters interactions other than dispersion interaction (Table ). Thus, dispersive interaction is found to be the key component in stabilizing the complexes which is in line with the majority of literatures on the nature of B‐H b ⋯π interaction …”
Section: Nature Of the Interactionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, in case of F‐substituted DB, favorable interaction (positive ΔE values) is predicted from B3LYP functional which encounters interactions other than dispersion interaction (Table ). Thus, dispersive interaction is found to be the key component in stabilizing the complexes which is in line with the majority of literatures on the nature of B‐H b ⋯π interaction …”
Section: Nature Of the Interactionsupporting
confidence: 88%
“…Thus, interactions other than dispersion are not strong enough to stabilize the complexes to a significant extent. Recent literatures also confirmed the primary role of dispersive interaction in stabilizing the complexes formed between DB and arene . However, the secondary role of other interactions cannot be ruled out from the calculated ΔE values in some of the complexes.…”
Section: Nature Of the Interactionmentioning
confidence: 84%
See 1 more Smart Citation
“…The electrostatic repulsion in these counterintuitive cases is overwhelmed by the stabilizing polarization, dispersion interaction, and most importantly, the charge transfer interaction, resulting eventually counterintuitively in an overall attraction. Similarly, the high-level ab initio and symmetry adapted perturbation theory (SAPT) [131] calculations on close B-H• • • π contacts, which have been observed in crystallographic structures of Ir-dithiolene-phosphine complexes containing a boron hydride cluster [132], have reinterpreted the nature of B-H• • • π contacts in this system. Although the characteristics of the B-H• • • π interaction have been known for decades, these authors argued that they disproved the widely-accepted view that these are attractive electrostatic interactions that arise as a consequence of the intermolecular interaction.…”
Section: Introductionmentioning
confidence: 85%
“…[12][13][14][15] Boranes and carboranes are recently targeted because of their potential to form BH � � � p interactions with the π-face of an arene. [16][17][18][19] It has been suggested that these BH � � � p interactions may be driven by a nonspecific weak dispersion contact, as for example based on restrained fit to the electrostatic potential and symmetryadapted perturbation theory studies [20,21] or molecular orbital analyses. [22] However, these approaches are not free from some arbitrariness, therefore they are generally not suited for deriving more definite conclusions on a particular bonding situation.…”
Section: Introductionmentioning
confidence: 99%